The Relationship between Land Subsidence and Water Use in Yazd-Ardakan Plain Using Sentinel-1 Images - Mohammadreza Goodarzi; Maryam Sabaghzadeh; Amirreza Rajabpour niknam (تحقیقات کاربردی علوم جغرافیایی)
In arid and semi-arid regions, groundwater is more important for humans and ecosystems than surface water. Land subsidence is caused by the pumping and uncontrolled use of groundwater in an area. When the extracted quantities are not replenished by rainfall, it leads to damages such as road failures, destruction of residential areas, railways, as well as water and gas pipelines. The Yazd-Ardakan plain is one of the main plains in Yazd province, hosting 75% of the province's population density and most industrial centers. Additionally, this plain has been subjected to a ban by the Ministry of Energy due to a sharp decline in groundwater levels. This study aimed to quantify and compare the extent of subsidence using four Synthetic Aperture Radar (SAR) images of the C-band from the Sentinel-1 satellite and the radar differential interferometry method from 2017 to 2021. The maximum subsidence recorded in 2017 was 13 cm, while in 2020 and 2021, it decreased to 9 cm, primarily concentrated in the Shamsi region between Meybod and Ardakan. Furthermore, to validate the satellite-derived results, they were compared with those obtained through accurate leveling methods conducted by the Iran National Cartographic Center. The study revealed that Sentinel images exhibit a strong capability to estimate the extent of subsidence. Considering the examination of groundwater consumption and depletion statistics in recent years, potential reasons for the reduction in subsidence in the study area could be attributed to management measures such as water transfer to this basin, alterations in agricultural practices, and a decrease in groundwater depletion compared to previous years in this region.